Brief research report: ETS-1 blockade increases ICAM-1 expression in activated human retinal endothelial cells - Tan, Alwin Chun Rong; Ma, Yuefang; Appukuttan, Binoy; Lower, Karen; Lumsden, Amanda L.; Michael, Michael Z.; Smith, Justine R.; Ashander, Liam M. (Frontiers in Ophthalmology, 2024)
Intercellular adhesion molecule 1 (ICAM-1) is a central cell adhesion molecule for retinal transendothelial migration of the leukocytes in non-infectious posterior uveitis. Inhibiting ICAM1 gene transcription reduces induction of ICAM-1 in inflamed retinal endothelium. Based on published literature implicating transcription factor ETS-1 as an activator of ICAM1 gene transcription, we investigated the effect of ETS-1 blockade on ICAM-1 levels in cytokine-stimulated human retinal endothelial cells. We first examined ICAM1 and ETS1 transcript expression in human retinal endothelial cells exposed to tumor necrosis factor-alpha (TNF-α) or interleukin-1beta (IL-1β). ICAM1 and ETS1 transcripts were increased in parallel in primary human retinal endothelial cell isolates (n = 5) after a 4-hour stimulation with TNF-α or IL-1β (p ≤ 0.012 and ≤ 0.032, respectively). We then assessed the effect of ETS-1 blockade by small interfering (si)RNA on cellular ICAM1 transcript and membrane-bound ICAM-1 protein. ETS1 transcript was reduced by greater than 90% in cytokine-stimulated and non-stimulated human retinal endothelial cell monolayers following a 48-hour treatment with two ETS-1-targeted siRNA, in comparison to negative control non-targeted siRNA (p ≤ 0.0002). The ETS-1 blockade did not reduce ICAM1 transcript expression nor levels of membrane-bound ICAM-1 protein, rather it increased both for a majority of siRNA-treatment and cytokine-stimulation conditions (p ≤ 0.018 and ≤ 0.004, respectively). These unexpected findings indicate that ETS-1 blockade increases ICAM-1 transcript and protein levels in human retinal endothelial cells. Thus ETS-1-targeting would be expected to promote rather than inhibit retinal transendothelial migration of leukocytes in non-infectious posterior uveitis.